Using online patient feedback to improve NHS services: the INQUIRE multimethod study - John Powell; Helen Atherton; Veronika Williams; Fadhila Mazanderani; Farzana Dudhwala; Steve Woolgar; Anne-Marie Boylan; Joanna Fleming; Susan Kirkpatrick; Angela Martin; Michelle van Velthoven; Anya de Iongh; et al. (National Institute for Health Research, 2019)
Background: Online customer feedback has become routine in many industries, but it has yet to be harnessed for service improvement in health care. Objectives: To identify the current evidence on online patient feedback; to identify public and health professional attitudes and behaviour in relation to online patient feedback; to explore the experiences of patients in providing online feedback to the NHS; and to examine the practices and processes of online patient feedback within NHS trusts. Design: A multimethod programme of five studies: (1) evidence synthesis and stakeholder consultation; (2) questionnaire survey of the public; (3) qualitative study of patients' and carers' experiences of creating and using online comment; (4) questionnaire surveys and a focus group of health-care professionals; and (5) ethnographic organisational case studies with four NHS secondary care provider organisations. Setting: The UK. Methods: We searched bibliographic databases and conducted hand-searches to January 2018. Synthesis was guided by themes arising from consultation with 15 stakeholders. We conducted a face-to-face survey of a representative sample of the UK population (n = 2036) and 37 purposively sampled qualitative semistructured interviews with people with experience of online feedback. We conducted online surveys of 1001 quota-sampled doctors and 749 nurses or midwives, and a focus group with five allied health professionals. We conducted ethnographic case studies at four NHS trusts, with a researcher spending 6-10 weeks at each site. Results: Many people (42% of internet users in the general population) read online feedback from other patients. Fewer people (8%) write online feedback, but when they do one of their main reasons is to give praise. Most online feedback is positive in its tone and people describe caring about the NHS and wanting to help it ('caring for care'). They also want their feedback to elicit a response as part of a conversation. Many professionals, especially doctors, are cautious about online feedback, believing it to be mainly critical and unrepresentative, and rarely encourage it. From a NHS trust perspective, online patient feedback is creating new forms of response-ability (organisations needing the infrastructure to address multiple channels and increasing amounts of online feedback) and responsivity (ensuring responses are swift and publicly visible). Limitations: This work provides only a cross-sectional snapshot of a fast-emerging phenomenon. Questionnaire surveys can be limited by response bias. The quota sample of doctors and volunteer sample of nurses may not be representative. The ethnographic work was limited in its interrogation of differences between sites. Conclusions: Providing and using online feedback are becoming more common for patients who are often motivated to give praise and to help the NHS improve, but health organisations and professionals are cautious and not fully prepared to use online feedback for service improvement. We identified several disconnections between patient motivations and staff and organisational perspectives, which will need to be resolved if NHS services are to engage with this source of constructive criticism and commentary from patients. Future work: Intervention studies could measure online feedback as an intervention for service improvement and longitudinal studies could examine use over time, including unanticipated consequences. Content analyses could look for new knowledge on specific tests or treatments. Methodological work is needed to identify the best approaches to analysing feedback. Study registration: The ethnographic case study work was registered as Current Controlled Trials ISRCTN33095169. Funding: This project was funded by the National institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 7, No. 38. See the NIHR Journals Library website for further project information.